Modelling of interceptor drainage effect on water table and salinity levels in agricultural area of Abyek Plain Iran - Ghorbani, Karim (2016)
Water and soil are two major elements in Nature that play critically important roles in agricultural production. Over the past decades, wide areas of irrigated lands have been faced with the problem of high groundwater tables which cause salinization and degradation of broad areas of irrigated or non-irrigated land. Due to land constraints and growing demand for food, it is essential to control the environmental instability and manage the precious natural resources. On the other hand, underground drainage schemes are widely being used to manage the groundwater table and reduce the salinity level in the arid and semi-arid regions, especially in Iran. Since the design and investigation of drainage system performance typically are costly and time consuming, a modelling approach can be a suitable technique to reduce the costs and at the same time offer quick access to highly accurate Results. In addition, employing a computer model can help to determine the hydrogeological parameters of aquifer and predict the groundwater flow behaviour in future conditions. Therefore, the main purpose of this research is to develop a practical technique in design of efficient drainage systems for implementation to protect agricultural area and solve the related problem of salinity using three-dimensional groundwater flow model (MODFLOW) and solute transport model (MT3D).For this purpose, a total of ninety-nine observational wells were installed adjacent to the existing drainage channel in the Abyek Plain, Iran to monitor groundwater fluctuation and changes in salinity level. Groundwater level was measured monthly from December 2010 to December 2014. In addition, the quality of water and soil was tested at every season (January, April, August. and November) during the four years. The analysis of the recorded data indicated that level of groundwater on the study site has been dropped in a wide - 500 m from the existing drainage system. Evaluation of measured data also indicted that the salinity level had been reduced substantially during the four-year period. The MODFLOW models that is supported by groundwater modelling system (GMS), was calibrated to the study area in two states, the steady state and transient state to reproduce the measured data for one year and three years, respectively. The calibrated model was used to predict the future conditions and possible changes in groundwater level. According to simulated results, water table can be lowered approximately 1.48 and 1.59 m in August 2015 and 2020, respectively. Six drainage scenarios together with existing drains were defined in the calibrated model to simulate the function of the drains separately. Simulated results revealed that installation of an additional parallel interceptor drainage system at a distance of 1000 m from the existing drainage scheme could be a most effective drainage design. This design is able to maintain the groundwater table at an acceptable level of ground surface and improve large areas of the study site compared to other designs. The solute transport model (MT3D) was also calibrated in the transient state to reproduce observed salinity data. The calibrated model was used to simulate magnitude of the electrical conductivity of groundwater from 1st January 2011 to 30th December 2013. The results of this study indicated that the model has the ability to accurately predict dissolved solids in groundwater. Results also revealed that reduction in salinity level varied in the range between 4.4 and 137.7 dS.m-1 during the three years. As a result, modelling can be a feasible technique for decision makers to design efficient drains in agricultural land faced with a high water table and salinity problem.